Klebsiella Pneumoniae, an Important Uropathogen: Prevalence and Antimicrobial Susceptibility Pattern - Dr. Payal Soni; Dr. Alka Nerurkar; Dr. Vicky Gandhi (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Urinary Tract Infections (UTIs) are amongst the 2nd most common infections after respiratory tract infections in community and healthcare settings (Hospital acquired infections). Klebsiella pneumoniae is the 2nd most common uropathogen after Escherichia coli. Klebsiella is known to have several virulence factors and resistant strains are rising which includes Extended-spectrum Beta-lactamase (ESBL) producing and Carbapenem-resistant strains. Aim of the study is to assess the prevalence of Klebsiella pneumoniae as an Uropathogen and their antimicrobial susceptibility pattern at a tertiary care hospital, Valsad.Material and Methods: Retrospective study is conducted including isolates of Klebsiella pneumoniae from urine samples received in microbiology laboratory at a tertiary care hospital, Valsad, Gujarat, India from January 2018 to December 2018. Processing of samples, isolation and identification of Klebsiella pneumoniae strains with Antimicrobial susceptibility testing were done using standard microbiology techniques.Result: Out of 576 urine samples received in 2018, 209 (36.28%) showed significant growth. Prevalence of Klebsiella pneumoniae as Uropathogen is 9.72% (n=576) and their antimicrobial susceptibility pattern shows higher resistance to β-lactum group (Penicillin, Cephalosporins and Carbapenem). Susceptibility is maximum against Chloramphenicol (87.5%) followed by Nitrofurantoin (64.29%), Amikacin (62.5%), Imipenem (60.71%), Meropenem (60.71%), Levofloxacin (57.14%) and Piperacillin/Tazobactum (57.14%).Conclusion: Klebsiella pneumoniae remains an important Uropathogen both in community and Hospital acquired infections. Resistance among Klebsiella pneumoniae strains shows upward trends over last few years. Increasing prevalence of ESBL producing and Carbapenem resistant strains creates alarming situation for healthcare system.